Court of Reflections, Golden Gate International Exposition, San Francisco (H.S. Crocker Co., Inc.)
Quiet pools repeat the exquisite colorings of the walls of the Court of Reflections at San Francisco's World's Fair. "Black light" directed on fluorescent paints and indirect colored lighting are responsible for the after-dark beauty of Treasure Island, site of the Fair.